Critical Reading and Creative Writing Literacy Learning Training Based on the RADEC Model to Improve Teachers' Pedagogical Competence - suharti, suharti; Faidin, Faidin; Rahmawan, Ardi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This Beginner Community Empowerment (PMP) is focused on critical reading and creative writing literacy learning training based on the RADEC model to improve the pedagogical competence of teachers in SMPN 1 Woha. The determination of this training is based on the low ability of teachers in implementing literacy learning that focuses on critical reading and creative writing, many teachers still prefer to use lecture methods and give assignments through worksheet. The goal to be achieved in the community service is to provide Critical Reading and Creative Writing literacy learning training Based on the RADEC Model to Improve the Pedagogical Competence of Teachers SMPN 1 Woha. Stages of the method, Socialization, Training, Application of technology, Mentoring and evaluation, in this case there are pretests and posttests to determine the teacher's understanding of the material. The results obtained from the implementation of this PMP activity as a whole got good and satisfactory results. Some components that were successfully achieved in the implementation of this activity include: 1) achievement of activity objectives as indicated by the level of participation of participant, pretest and posttest results, questionnaires, and, 2) achievement of planned material targets, as well as technology application activities, mentoring to evaluation of literacy learning carried out by teachers were carried out well as indicated by the planning and implementation of critical reading literacy and creative writing based on the RADEC model by teachers, literacy materials taken from various literacy e-book platforms, packaged in Barcode for critical reading and creative writing activities.